Fuzzy n-fold obstinate ideals in mv -algebras - Fereshteh Forouzesh (Journal of Hyperstructures, 2019)
Abstract. In this paper, we introduce the notion of n-fold Boolean ideals of an MV -algebra and consider the quotient algebras induced by n-fold Boolean ideals. Also we prove that I is a n-fold Boolean ideal of an MV -algebra if and only if A/I is a n+1-bounded MV -algebra if and only if A/I is a subdirect product of algebras Lk,with 2 ≤ k ≤ n.Finally, we introduce the notion of fuzzy n-fold obstinate ideals in MV -algebras. We give some characterizations of fuzzy n-fold obstinate ideals.